Tubulin inhibitors in non-small cell lung cancer: looking back and forward. (23rd May 2016) - Ferrara, R.; Pilotto, S.; Peretti, U.; Caccese, M.; Kinspergher, S.; Carbognin, L.; Karachaliou, N.; Rosell, R.; Tortora, G.; Bria, E.
ABSTRACT: Introduction : Although the advent of target therapy for lung cancer has brought about outstanding results, this benefit is confined to a subgroup of molecularly selected patients, whereas for most non-small cell lung cancer (NSCLC) patients, chemotherapy still represents the milestone of treatment. Since their introduction into clinics, microtubule targeting agents (MTA), including vinca alkaloids and taxanes, have been extensively used for NSCLC in different settings and combinations. Areas Covered : In this review, MTA are classified according to their mechanism of action, with a focus on the most common mechanisms of resistance. Moreover, an overview of the most remarkable clinical data regarding MTA in adjuvant, neoadjuvant and advanced setting is provided. Finally, the novel mitotic kinases inhibitors are described according to their different mechanism of action and clinical activity compared to MTA. Expert Opinion : Unfortunately, the awaited benefit deriving from the actually available chemotherapeutic regimens for advanced NSCLC has reached a plateau. In this scenario, the identification of reliable predictive biomarkers represents a major challenge. Moreover, different schedules for MTA administration are currently under investigation, such as the combination of MTA with other drugs able to bypass the resistance derived from the 'mitotic slippage' and the use of metronomic administration of spindle poisons with anti-angiogenic or immunomodulatory agents.